Analysis on the Influence of the Epidemic on the Education in China - Xiao, Chunchen; Li, Yi (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
The sudden outbreak of the novel corona virus, Covid-19, brought a lot of loss to China and the Chinese people. To contain the epidemic, people had to stay where they were. They could not go back to work or to school. Some dormitories in the universities were requisitioned temporarily as ward for Covid-19-infectious patient. The offline courses were due many reasons infeasible, what brought unexpected changes to education. With the analysis on the latest news about policies and relevant data, this paper focuses on the impact of the epidemic caused by Covid-19 on the education in China. In order to make the influence clearly and comprehensive, the education in China is divided into varies of parts, namely, compulsory education, extracurricular education and higher education, which further divided into study abroad and study inland. And the influence concentrates on the teaching and learning-effect, the transformation of the teaching forms, the employment of the students and the enrollment of the schools. The analysis result shows that the compulsory education is the less affected than higher education, because the students who are taking compulsory education do not face the employment pressure. Although online courses are lack of supervision, so that the learning effect of the students with poor self-control will get worse and the gap between good students and bad students will widen, after they return to school and take the normal offline courses, the "Matthew Effect" will be eliminated. In comparison, the employment and enrollment stress that the students and universities are suffering from will last for a long time. Besides, the extracurricular education also encounter irreversible loss, because companies that incapable to open online courses are forced to close. In addition, problems of the online courses platforms are found through the research. Professional teaching platforms are still a blank and urged to be developed. In a word, despite all the impact on the Chinese education, education sector is still an optimistic area because of the hope and potential brought and presented by the online education.